2014
DOI: 10.1152/ajpheart.00452.2014
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 reverses reactivity and Ca2+ sensitivity induced by ET-1, TNF-α, and IL-6 in the human pulmonary artery

Abstract: monary hypertension (PH) is a rare and progressive disease characterized by an inflammatory status and vessel wall remodeling, resulting in increased pulmonary artery resistance. During the last decade, treatments have been proposed; most of them target the endothelial pathways that stimulate smooth muscle cell relaxation. However, PH remains associated with significant morbidity. We hypothesized that inflammation plays a crucial role in the severity of the abnormal vasoconstriction in PH. The goal of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…The DHA metabolite Resolvin D1 has recently been shown to reduce inflammation markers and hyperreactivity in human pulmonary artery upon in-vitro treatment [17]. To strengthen these reports, the current (A) Experimental design and treatments.…”
Section: Experimental Design and Preliminary Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The DHA metabolite Resolvin D1 has recently been shown to reduce inflammation markers and hyperreactivity in human pulmonary artery upon in-vitro treatment [17]. To strengthen these reports, the current (A) Experimental design and treatments.…”
Section: Experimental Design and Preliminary Resultsmentioning
confidence: 99%
“…In a previous study, we also demonstrated that MAG-DHA needs to be metabolized to exert its beneficial action, and that one of its metabolites, resolving D1 (RvD1), leads an enhanced expression of GPR32 [17], previously identified as the RvD1 receptor [24]. In order to further assess the manner in which MAG-DHA may counteract the effects of MCT treatment on the expression of these key biological markers, PASM cell lysates were fractionated using differential ultracentrifugations from which microsomal fractions were used to detect expression of membrane proteins (TMEM16A and GPR32) while cytosolic fractions were used to detect the expression of HIF1-α.…”
Section: Pharmacological Treatment Regulates the Expression Of Biologmentioning
confidence: 89%
See 3 more Smart Citations